Optimizing omentoplasty for management of chronic pelvic sepsis by intra‐operative fluorescence angiography: a comparative cohort study. (17th August 2020) - Slooter, M. D.; Blok, R. D.; de Krom, M. A.; Buskens, C. J.; Bemelman, W. A.; Tanis, P. J.; Hompes, R.
Abstract: Aim: Pelviperineal wound complications frequently occur after salvage surgery for chronic pelvic sepsis despite using an omentoplasty. Sufficient perfusion of the omentoplasty following mobilization is essential for proper healing. This study investigated the impact on short‐term clinical outcomes of fluorescence angiography (FA) using indocyanine green for assessment of omental perfusion in patients undergoing salvage surgery. Method: This was a comparative cohort study including consecutive patients who underwent combined abdominal and transanal minimally invasive salvage surgery with omentoplasty at a national referral centre for chronic pelvic sepsis between December 2014 and August 2019. The historical and interventional cohorts were defined based on the date of introduction of FA in April 2018. The primary outcome was pelviperineal non‐healing, defined by the presence of any degree of pelviperineal infection at the final postoperative evaluation. Results: Eighty‐eight patients underwent salvage surgery with omentoplasty for chronic pelvic sepsis, of whom 52 did not have FA and 36 did have FA. The underlying primary disease was Crohn's disease ( n = 50) or rectal cancer ( n = 38), with even distribution among the cohorts ( P = 0.811). FA led to a change in management in 28/36 (78%) patients. After a median of 89 days, pelviperineal non‐healing was observed in 22/52 (42%) patients in the cohort without FA and in 8/36 (22%) patients in the cohort with FA ( P = 0.051). Omental necrosis was found during reoperation in 3/52 and 0/36 patients, respectively ( P = 0.266). Conclusion: After introduction of FA to assess perfusion of the omentoplasty, halving of the pelviperineal non‐healing rate was observed in patients undergoing salvage surgery for chronic pelvic sepsis.